HOMONYM DISTRIBUTION IN ẸDO: A CASE OF THE VERB "GBÈ" - Enobakhare, Richard; Evbuomwan, Osaigbovo Obed (EBSU Journal of Social Sciences and Humanities, 2024)
This paper examines the various homonymous forms of the Ẹdo verb gbè. The study investigates the homonymous forms of the verb gbè in different contexts and how they are distributed within its semantic field in the language. The data available to the study comprises different homonyms of the gbè verb that were sourced from the Ẹdo native speakers, distributed across different demographic variables. The data were solicited through interviews, family, and other group discussions on several everyday topical issues that provide the informants with the appropriate contexts in which they can use the language in normal free-flowing everyday conversations. The homonymous lexical items that were observed in the recorded speeches were later extracted and sorted out, paying attention to the appropriate context in which they have been used. The extracted data were thereafter observed and objectively described. The analysis shows that the homonymous forms of the Ẹdo gbè verb are ordered along the lines of the different contexts of usage and each is further organized into sub-contextual fields. The paper concludes that homonym distributions in the Ẹdo language are ordered into various contextual and sub-contextual fields that account for their effective disambiguation and conversational appropriateness.